Connecting to global markets challenges and opportunities; case studies presented by WTO chair-holders - Jansen, Marion; Sadni Jallab, Mustapha; Smeets, Maarten (WTO, 2014)
Developing countries and emerging economies have played an ever-expanding role in world trade flows in recent decades but they still face a number of constraints in connecting to global markets. In this volume, members of the WTO’s academic network in developing countries — the WTO Chairs Programme — identify major challenges in their respective countries and how to overcome them
Gesehen am 09.12.2016
Enth. 14 Beitr